Contributing to Nature's Recovery through Urban Agriculture - Jamie Matthews; Afshin Akhtar-Khavari (Vasyl Stefanyk Precarpathian National University, 2018)
The paper analyses the legally established practice of agriculture has been forced out of the urban environment as land value increases with higher population densities. It's stated, that cities and surrounding urban environments have grown dependent upon regional areas and industrial agricultural practices to provide food for their increasing populations. Most commonly, urban agriculture is practiced by third world nations as a first line of defence against hunger and malnutrition or as poverty alleviation in times of economic stress. This paper argues that the practice of urban agriculture contributes to vital environmental recovery necessary in this, the geological age of the Anthropocene. As human activity continues to impact the functioning of earth systems at the planetary scale, we must actively assist nature to recover rather than assume that our existing environmental protection and conservation strategies are effective in preserving the natural environment.